Wide-temperature-range anti-deformation die-casting high-aluminum lining plate preform and preparation method thereof
Patent Information
- Application Number
- CN202611196344.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-07
- Publication Date
- 2026-10-27
AI Technical Summary
[0003]针对现有技术存在的大尺寸衬板预制件在宽温域服役时易发生对角线扭曲、烧结收缩不均及高温蠕变变形的问题,本申请通过一种宽温域抗变形模铸高铝衬板预制件及其制备方法,实现预制件全温域形变均匀、高温结构稳定及高精度装配
[0014]本申请提供的宽温域抗变形模铸高铝衬板预制件及其制备方法,通过材质配方体系与制备烘烤工艺的协同优化,有效解决了宽温域下的变形与蠕变难题。在材质方面,采用多级连续级配的高铝骨料构建均匀骨架,消除成型疏密差异;引入红柱石作为微膨胀组分,利用其在1200℃~1550℃区间的可控相变微膨胀效应,精准抵消基质烧结收缩;复配α-Al2O3抗蠕变超细粉体,填充孔隙并强化高温陶瓷结合网络,显著提升1580℃高温下的结构强度与抗蠕变能力;采用低钙高铝水泥作为结合剂,规避钙长石等低熔点相生成,降低养护与升温过程中的残余应力,从材质内部根源上消除差异化收缩与高温软化风险。在工艺方面,采用包含低温除水、中温均稳、中高温匀速烧结、高温稳态致密及对称密闭缓冷的五段式对称梯度烘烤制度,并全程严格控制对角温差,确保预制件受热均匀、应力同步释放、烧结速率一致,彻底杜绝因非对称热场导致的对角线扭曲与翘曲缺陷。该技术方案使预制件重烧线变化率稳定控制在±0.12%以内,全域密度差值≤0.02g/cm³,实现了大尺寸宽温域抗变形模铸高铝衬板预制件在1200℃~1580℃宽温域下的高尺寸稳定性与长寿命服役。
Abstract
Description
Technical Field
[0001] This invention relates to the field of refractory material preparation and refractory baking process technology, specifically to a wide-temperature-range deformation-resistant die-cast high-alumina liner preform and its preparation method. Background Technology
[0002] In the field of metallurgical casting, large-size high-alumina refractory preforms are often used as working liners in a wide temperature range of 1200℃ to 1580℃. These preforms require excellent dimensional stability, high-temperature creep resistance, and uniform sintering performance. However, existing traditional high-alumina preforms generally suffer from poor material structure uniformity, significant anisotropy in sintering shrinkage, and insufficient high-temperature thermal stability. Specifically, the unreasonable aggregate gradation in traditional formulations leads to uneven density after molding, a lack of directional anti-shrinkage and anti-creep components in the matrix, and the tendency of ordinary bonding systems to generate low-melting-point phases. This makes the preforms highly susceptible to irreversible deformations such as diagonal twisting, warping, and localized unevenness under high-temperature baking and alternating high- and low-temperature conditions. Furthermore, existing preparation and baking processes are relatively crude, resulting in uneven molding vibration, residual curing stress, and asymmetrical baking temperature fields, further exacerbating asymmetric thermal deformation and residual stress-release-type warping, severely affecting the assembly accuracy and service life of large-size liners. Therefore, there is an urgent need to develop a preform and its supporting manufacturing process that can maintain uniform deformation, high-temperature structural stability and no diagonal deformation over a wide temperature range. Summary of the Invention
[0003] To address the problems of diagonal distortion, uneven sintering shrinkage, and high-temperature creep deformation that easily occur in large-size liner preforms during wide-temperature-range service, this application proposes a wide-temperature-range anti-deformation die-cast high-alumina liner preform and its preparation method, which achieves uniform deformation across the entire temperature range, stable high-temperature structure, and high-precision assembly of the preform.
[0004] To achieve the above objectives, this application adopts the following technical solution: A wide-temperature-range, deformation-resistant die-cast high-alumina liner preform, based on 100% dry material weight, comprises the following raw materials: 70%~90% high-alumina aggregate; 3%~10% micro-expansion component; 1%~8% creep-resistant ultrafine powder; and 4%~10% low-calcium binder.
[0005] Preferably, the micro-expansion component includes andalusite; the creep-resistant ultrafine powder includes α-Al2O3; and the low-calcium binder includes low-calcium high-alumina cement, wherein the mass percentage of Al2O3 in the low-calcium high-alumina cement is ≥80%.
[0006] Preferably, based on the total dry weight of 100%, the content of andalusite is 4%~8%, and the particle size is 150~250 mesh; the content of α-Al2O3 is 2%~5%, and the particle size is 1000~1500 mesh; and the content of low-calcium high-alumina cement is 5%~8%.
[0007] Preferably, the high-alumina aggregate comprises a multi-stage continuous gradation structure, which includes coarse aggregate, medium aggregate, fine aggregate, and high-alumina fine powder. Based on 100% of the total dry weight, the coarse aggregate has a particle size of 3-5 mm and a content of 15%-30%; the medium aggregate has a particle size of 1-3 mm and a content of 15%-35%; the fine aggregate has a particle size of 0-1 mm and a content of 10%-25%; and the high-alumina fine powder has a particle size of 200-400 mesh and a content of 10%-20%.
[0008] Preferably, based on the total weight of dry materials (100%), the content of coarse aggregate is 20%~26%; the content of medium aggregate is 22%~28%; the content of fine aggregate is 16%~22%; and the content of high-alumina fine powder is 12%~18%.
[0009] Preferably, based on the total weight of dry materials (100%), the raw materials for preparation also include: 0.5%~2% silica powder; 0.1%~0.5% composite water-reducing agent; 0.1%~0.5% high-temperature resistant and explosion-proof fiber; and 0.5%~2% curing uniformity regulator.
[0010] Preferably, the bulk density of the wide-temperature-range anti-deformation molded high-alumina liner preform is ≥2.65g / cm³, the density difference across the entire range is ≤0.02g / cm³, and the linear change rate after reheating at 1550℃ for 3h is within ±0.12%.
[0011] Preferably, the wide-temperature-range deformation-resistant die-cast high-alumina liner preform is a die-cast high-alumina liner, and the die-cast high-alumina liner has a large-size rectangular structure.
[0012] Furthermore, this application also provides a method for preparing a wide-temperature-range, deformation-resistant, die-cast high-alumina liner preform as described above, comprising: premixing and stirring the raw materials to obtain a mixture; vibrating and molding the mixture and curing it under constant temperature and humidity to obtain a preform blank; and performing a five-segment symmetrical gradient baking on the preform blank to obtain the wide-temperature-range, deformation-resistant, die-cast high-alumina liner preform; wherein the five-segment symmetrical gradient baking sequentially includes: a low-temperature dehydration segment, with a temperature range of room temperature to 200°C; a medium-temperature stable segment, with a temperature range of 200°C to 600°C; a medium-high temperature uniform sintering segment, with a temperature range of 600°C to 1200°C; a high-temperature stable densification segment, with a temperature range of 1200°C to 1580°C; and a symmetrical closed slow cooling segment, with a temperature range of 1580°C to room temperature.
[0013] Preferably, in the five-segment symmetrical gradient baking process: the heating rate of the low-temperature dehydration section is 8~12℃ / h, and the holding time is 1~3h; the heating rate of the medium-temperature uniform sintering section is 15~20℃ / h, and the holding time is 2~4h; the heating rate of the medium-high temperature uniform sintering section is 20~25℃ / h; the heating rate of the high-temperature steady-state densification section is 12~18℃ / h, and the holding time is 3~5h; the cooling rate of the symmetrical sealed slow cooling section is ≤15℃ / h; and the diagonal temperature difference is controlled to be ≤15℃ throughout the entire five-segment symmetrical gradient baking process. Beneficial effects
[0014] The wide-temperature-range, deformation-resistant high-alumina liner precast component and its preparation method provided in this application effectively solve the deformation and creep problems in a wide temperature range through the synergistic optimization of the material formulation system and the preparation and baking process. In terms of materials, a multi-level continuously graded high-alumina aggregate is used to construct a uniform skeleton, eliminating differences in molding density; andalusite is introduced as a micro-expansion component, utilizing its controllable phase transformation micro-expansion effect in the 1200℃~1550℃ range to precisely offset matrix sintering shrinkage; α-Al2O3 anti-creep ultrafine powder is compounded to fill pores and strengthen the high-temperature ceramic bonding network, significantly improving structural strength and creep resistance at 1580℃; low-calcium high-alumina cement is used as a binder to avoid the formation of low-melting-point phases such as anorthite, reducing residual stress during curing and heating, and eliminating the risk of differential shrinkage and high-temperature softening from the root cause of the material. In terms of process, a five-stage symmetrical gradient baking system is adopted, including low-temperature dehydration, medium-temperature uniform sintering, medium-high temperature uniform sintering, high-temperature steady-state densification, and symmetrical closed slow cooling. The diagonal temperature difference is strictly controlled throughout the process to ensure uniform heating of the preforms, synchronous stress release, and consistent sintering rates, completely eliminating diagonal distortion and warping defects caused by asymmetrical thermal fields. This technical solution enables the reheat linear change rate of the preforms to be stably controlled within ±0.12%, and the overall density difference to be ≤0.02g / cm³, achieving high dimensional stability and long service life for large-size, wide-temperature-range, deformation-resistant molded high-alumina liner preforms within a wide temperature range of 1200℃~1580℃. Detailed Implementation Example 1
[0015] This embodiment provides a method for preparing a wide-temperature-range deformation-resistant high-alumina molded liner preform. The wide-temperature-range deformation-resistant high-alumina molded liner preform prepared by this method is particularly suitable for molded mold working liners in a wide temperature range environment of 1200℃ to 1580℃.
[0016] Regarding the raw material formulation, based on the total dry weight of 100%, the raw materials include: 70%~90% high-alumina aggregate; 3%~10% micro-expansion component; 1%~8% creep-resistant ultrafine powder; and 4%~10% low-calcium binder. Specifically, in this embodiment, the high-alumina aggregate adopts a multi-level continuous gradation structure, with a total content of 82%, of which coarse aggregate with a particle size of 3~5mm accounts for 23%, medium aggregate with a particle size of 1~3mm accounts for 25%, fine aggregate with a particle size of 0~1mm accounts for 19%, and high-alumina fine powder with a particle size of 325 mesh accounts for 15%; the micro-expansion component is selected from 200-mesh andalusite fine powder, with a content of 6%; the creep-resistant ultrafine powder is selected from 1250-mesh α-Al2O3 ultrafine powder, with a content of 3%; and the low-calcium binder is selected from CA-80 low-calcium high-alumina cement with an α-Al2O3 mass percentage of ≥80%, with a content of 6.2%. In addition, the raw materials used in the preparation include: 1% silica fume, 0.3% composite water-reducing agent, 0.2% high-temperature resistant and explosion-proof fiber, and 1.3% curing uniformity regulator. This specific multi-stage continuous gradation design utilizes coarse aggregate to construct a high-temperature skeleton, medium and fine aggregate to fill the voids, and combined with the micro-filling effect of ultrafine powder, it can eliminate the density difference after molding from the physical stacking level, ensuring uniform density throughout the preform. Andalusite undergoes a mullite-like phase transformation in the 1200℃~1550℃ range, producing micro-expansion, which precisely offsets the sintering shrinkage of the matrix; α-Al2O3 ultrafine powder promotes the formation of ceramic bonding network at high temperatures, improving creep resistance; low-calcium high-alumina cement avoids the formation of low-melting-point phases such as calcium feldspar. The three work synergistically to solve the deformation and softening problems in a wide temperature range from the root of the material.
[0017] In terms of the preparation process, the raw materials are first premixed and stirred to obtain a mixture. Specifically, α-Al2O3 ultrafine powder and silica powder are premixed to ensure the uniform dispersion of the ultrafine powder in the matrix. Then, other dry materials are added and forced dry mixing is performed for 2 minutes, followed by wet mixing for 3.5 minutes with water accounting for 5.0% of the total weight of the dry materials to ensure that the mud has good rheological and thixotropic properties. Next, the mixture is vibrated and cured at constant temperature and humidity to obtain the preform blank. In this embodiment, a whole flat vibrating table is used for uniform vibration molding, and the surface is lightly pressed and smoothed to eliminate surface pores. After molding, it is left to stand for 24 hours before demolding, and then placed in a constant temperature and humidity environment of 22°C and 92% for 7 days to allow the low-calcium high-alumina cement to fully hydrate and form a stable bonding strength, while releasing residual molding stress.
[0018] Regarding the baking process, the preform blank is subjected to a five-stage symmetrical gradient baking process to obtain a wide-temperature-range, deformation-resistant, die-cast high-alumina liner preform. This baking regime is a key external process condition for eliminating diagonal deformation in large-size preforms in this application, and specifically includes the following five stages: Step S100, low-temperature dehydration stage, with a temperature range from room temperature to 200℃. In this stage, the heating rate is 10℃ / h, and the temperature is held at 200℃ for 2 hours. This stage aims to slowly remove free water and some crystal water from the green body, avoiding microcracks caused by excessive internal vapor pressure due to rapid moisture evaporation.
[0019] Step S200, the medium-temperature stabilization stage, with a temperature range of 200℃ to 600℃. During this stage, the heating rate is 18℃ / h, and the temperature is held at 600℃ for 3 hours. This temperature range is crucial for the dehydration and decomposition of the binder and the oxidation of organic matter. Appropriate temperature control helps to unify the temperature field inside and outside the billet, eliminating the thermal stress gradient caused by lag in heat conduction.
[0020] Step S300, the medium-high temperature uniform sintering section, with a temperature range of 600℃ to 1200℃. In this stage, the heating rate is 22℃ / h, and no isothermal point is set. During this stage, the matrix begins initial sintering, and the micro-expansion effect of the andalusite phase transformation gradually initiates. The uniform heating rate ensures a dynamic balance between the expansion reaction and sintering shrinkage.
[0021] Step S400, the high-temperature steady-state densification stage, has a temperature range of 1200℃ to 1580℃. In this stage, the heating rate is 15℃ / h, and the temperature is held at 1580℃ for 4 hours. This is the core stage for the preform to achieve its final high-temperature performance. α-Al2O3 reacts with the matrix to form a high-strength ceramic bonding phase, and the sufficient holding time ensures the completion of the densification process and the homogenization of the microstructure.
[0022] Step S500, symmetrical closed slow cooling section, with a temperature range from 1580℃ to room temperature. During this stage, the cooling rate is controlled to within 15℃ / h. Throughout the entire five-segment symmetrical gradient baking process, the temperature difference between any two diagonal positions within the kiln is strictly controlled to ≤15℃ through precise control of the furnace heating element layout and air circulation system. This full-process symmetrical thermal field management completely eliminates diagonal distortion and warping defects caused by asymmetrical cooling contraction.
[0023] The wide-temperature-range, deformation-resistant die-cast high-alumina liner preform prepared by the above process has a bulk density of 2.72 g / cm³, a density difference of only 0.02 g / cm³ across the entire range, a linear shrinkage rate of ±0.10% after reheating at 1550℃ for 3 hours, and a high-temperature flexural strength of 6.8 MPa at 1500℃. Test results show that the preform exhibits no diagonal twisting or warping after baking, and its dimensional accuracy fully meets the assembly requirements for large-size rectangular die-cast high-alumina liners. Furthermore, it demonstrates structural stability and no creep deformation under high-temperature conditions of 1580℃, verifying the effectiveness of the synergistic effect of the material formulation and the five-segment symmetrical gradient baking process described in this application.
[0024] Example 2 This embodiment provides another method for preparing wide-temperature-range, deformation-resistant, molded high-alumina liner precast components. In this embodiment, the proportions of the raw materials are adjusted to values close to the range boundary, based on a total dry weight of 100%. Specifically, the micro-expansion component is selected from 200-mesh andalusite powder, with its content adjusted to 10%; the creep-resistant ultrafine powder is selected from 1250-mesh α-Al2O3 ultrafine powder, with its content adjusted to 1%; the low-calcium binder is still selected from CA-80 low-calcium high-alumina cement with an Al2O3 mass percentage ≥80%, with its content adjusted to 4.5%. In the multi-stage continuous gradation structure of the high-alumina aggregate, the content of coarse aggregate with a particle size of 3~5mm is adjusted to 30%, the content of medium aggregate with a particle size of 1~3mm is adjusted to 15%, the content of fine aggregate with a particle size of 0~1mm is adjusted to 10%, and the content of high-alumina fine powder with a particle size of 325 mesh is adjusted to 20%. In addition, the proportions of auxiliary additives were adjusted accordingly to the boundary values: the content of silica powder was 2%, the content of composite water-reducing agent was 0.1%, the content of high-temperature resistant explosion-proof fiber was 0.5%, and the content of curing uniformity regulator was 0.5%.
[0025] The preparation method and baking process of this embodiment are completely consistent with those of Example 1, that is, the same premixed ultrafine powder, forced stirring, integral plate vibration molding, constant temperature and humidity curing and five-stage symmetrical gradient baking system are used, and the diagonal temperature difference is controlled ≤15℃ throughout the process.
[0026] From the perspective of microstructural adaptability, when the andalusite content is increased to the upper limit of 10%, the amount of mullite phase transformation expansion generated in the 1200℃~1550℃ range increases significantly. At this point, combined with a higher content (20%) of high-alumina fine powder, it can effectively fill the micropores caused by expansion and buffer local stress concentration, preventing structural loosening caused by excessive expansion. Although the α-Al2O3 ultrafine powder content is reduced to the lower limit of 1%, resulting in a decrease in the density of the ceramic bonding network formed at high temperatures, the matrix can still maintain sufficient high-temperature structural stability under the support of the tightly packed skeleton constructed by the multi-level continuous graded aggregate. At the same time, the coarse aggregate content is increased to 30%, which strengthens the creep resistance of the rigid skeleton, while the lower amount of composite water-reducing agent (0.1%) avoids the mud segregation phenomenon that may occur under high aggregate specific surface area, ensuring the homogeneity of the formed green body.
[0027] Testing revealed that the bulk density of the wide-temperature-range, deformation-resistant high-alumina liner preform prepared in this embodiment was 2.66 g / cm³, the density difference across the entire temperature range was 0.02 g / cm³, the linear shrinkage rate after reheating at 1550℃ for 3 hours was +0.11%, and the high-temperature flexural strength at 1500℃ was 5.2 MPa. Compared to Example 1, although the performance indicators decreased slightly, the linear shrinkage rate after reheating remained stably controlled within ±0.12%, and the density difference across the entire temperature range did not exceed the limit of 0.02 g / cm³. Furthermore, the liner did not exhibit diagonal twisting or warping deformation after baking. This indicates that even when the content of key components deviates from the optimal implementation point and approaches the range boundary, through the synergistic adaptation of each component and the guarantee of the five-segment symmetrical gradient baking process, the preform can still meet the basic dimensional stability and creep resistance requirements for service in a wide temperature range of 1200℃~1580℃, fully demonstrating the robustness and reliability of the technical solution of this application within a wide parameter range.
[0028] Example 3 This embodiment aims to verify the technical stability of the wide-temperature-range, deformation-resistant, die-cast high-alumina liner preform when its performance parameters are at critical levels. Unlike the optimal implementation method in Embodiment 1, this embodiment intentionally brings the product performance close to the qualified threshold by fine-tuning the preparation process parameters, thereby providing direct experimental evidence for limiting performance indicators and establishing the robustness boundary of the technical solution.
[0029] In the specific preparation process, the raw material formula remained consistent with that of Example 1, namely, the same multi-stage continuous gradation high-alumina aggregate, andalusite micro-expansion component, α-Al2O3 creep-resistant ultrafine powder, and low-calcium binder system were used. However, the following critical conditions were adjusted in the molding and baking stages: in the vibration molding stage, the vibration frequency of the vibration table was lowered to the minimum limit that could maintain basic molding, simulating the lower limit of energy fluctuations that may occur in industrial production; in the medium-temperature stable section of the five-segment symmetrical gradient baking, the constant temperature time was shortened to the lower limit of the process allowable value of 2 hours, and the heating rate, holding time, and diagonal temperature difference control (≤15℃) of the remaining baking stages were strictly implemented according to the parameters of Example 1.
[0030] From a microscopic perspective, the reduction in vibration energy slightly decreases the initial packing density between coarse aggregate and fine powder, resulting in a small number of incompletely filled micropores in the matrix. Furthermore, the shortened isothermal time in the intermediate temperature range causes a slight difference in the progress of the dehydration and decomposition reaction of the low-calcium, high-alumina cement along the thickness of the green body. The residual trace amounts of bound water rapidly escape in the high-temperature sintering section, generating a very weak internal stress gradient. The combination of these two factors directly leads to a decrease in the macroscopic properties of the final product. Actual measurements show that the bulk density of the wide-temperature-range, deformation-resistant, molded high-alumina liner precast component prepared in this embodiment is 2.65 g / cm³, the density difference across the entire range is 0.02 g / cm³, and the reheat linear change rate at 1550℃ for 3 hours is +0.11%. All of these indicators fall precisely at the critical point of their defined ranges.
[0031] Despite being at a critical performance level, the preform maintained good geometric integrity after baking and cooling, exhibiting no diagonal distortion or warping deformation, and its dimensional accuracy met assembly requirements. This result strongly demonstrates that even when the forming density and sintering uniformity are at their lower limits, as long as the phase transformation micro-expansion effect of andalusite and the high-temperature skeleton strengthening effect of α-Al2O3 in the material system remain, and the diagonal temperature difference throughout the baking process is effectively controlled, the stress balance mechanism inside the preform will not fail.
[0032] Comparative Example 1 This comparative example aims to verify the crucial role of the micro-expansion component in the wide-temperature-range deformation resistance of the high-alumina liner precast components. By comparing with Example 1, the difference in technical effect when the micro-expansion component is missing from the raw materials is examined. Specifically, in the raw material formulation of this comparative example, the 200-mesh andalusite powder used in Example 1 was completely removed. Its original proportion of 6% of the total dry weight was replaced by an equal amount of high-alumina powder to maintain the balance of the total dry weight. Except for the above adjustment, the types and contents of the other raw materials are strictly consistent with those of Example 1, including multi-grade continuously graded high-alumina aggregate, 1250-mesh α-Al2O3 creep-resistant ultrafine powder, CA-80 low-calcium high-alumina cement, and various auxiliary additives. Meanwhile, the preparation process also follows the scheme of Example 1, namely, adopting the same premixing, vibration molding, and constant temperature and humidity curing process, and implementing a five-stage symmetrical gradient baking regime including low-temperature dehydration, medium-temperature stabilization, medium-high temperature uniform sintering, high-temperature steady-state densification, and symmetrical closed slow cooling. The diagonal temperature difference is also maintained at ≤15℃ throughout the process. This strict single-variable control design ensures that the degradation of the final product performance is only attributed to the absence of andalusite component, thereby enabling accurate assessment of the technical contribution of this micro-expansion component.
[0033] Testing revealed significant performance defects in the wide-temperature-range, deformation-resistant high-alumina molded liner preform prepared in this comparative example. Its linear shrinkage rate after reheating at 1550℃ for 3 hours reached -0.35%, far exceeding the acceptable range of ±0.12%. The liner exhibited obvious diagonal warping after baking and cooling, with a difference of 3.5 mm between the two diagonals, and significant flatness deviation, failing to meet the precision assembly requirements for large-size molded liners. Although the bulk density was 2.70 g / cm³, close to the level of Example 1, the internal structural distortion caused by uneven sintering shrinkage resulted in a decrease in its high-temperature flexural strength at 1500℃ to 4.1 MPa, and the overall density difference increased to 0.05 g / cm³, indicating the presence of significant stress concentration areas within the material.
[0034] From a microscopic perspective, the root cause of the aforementioned failure phenomenon lies in the absence of the micro-expansion effect of the mullite phase transformation of andalusite within the temperature range of 1200℃ to 1550℃. During the sintering process of the liner preform, the fine powder components and binder in the matrix undergo significant liquid-phase sintering and solid-phase reactions at high temperatures, accompanied by a non-negligible volume shrinkage. In Example 1, andalusite particles transform in situ into mullite within this temperature range, accompanied by a volume expansion of approximately 3% to 5%. This expansion behavior forms a precise dynamic compensation mechanism with the sintering shrinkage of the matrix in both time and space, effectively offsetting the net shrinkage and alleviating internal thermal stress. However, in this comparative example, due to the lack of this active expansion source, the cumulative shrinkage of the matrix over a wide temperature range is not compensated at all, resulting in excessive residual tensile stress in the preform during cooling. More importantly, due to the inherent differences in heat dissipation conditions and heat transfer paths in different parts of the large-size liner, this uncompensated shrinkage exhibits asynchronous behavior in the diagonal direction of the sheet. Even if the external baking temperature field is symmetrically controlled, the endogenous stress gradient generated within the material due to the inconsistent shrinkage rate is still sufficient to disrupt the geometric equilibrium, ultimately inducing irreversible diagonal distortion and warping deformation. This counter-indication strongly proves that, under wide temperature range service conditions of 1200℃~1580℃, the andalusite micro-expansion component is not a dispensable auxiliary additive, but an indispensable core functional component for achieving dimensional stability and deformation resistance of precast components.
[0035] Comparative Example 2 This comparative example aims to verify the crucial role of creep-resistant ultrafine powder in the high-temperature structural stability of wide-temperature-range, deformation-resistant molded high-alumina liner precast components. By comparing it with Example 1, the difference in technical effect when the creep-resistant ultrafine powder is absent from the raw materials is examined. Specifically, in the raw material formulation of this comparative example, the 1250-mesh α-Al₂O₃ ultrafine powder used in Example 1 was completely removed. Its original 3% proportion of the total dry weight was replaced by an equal amount of high-alumina fine powder to maintain the overall dry weight balance. Except for the above adjustment, the types and contents of the remaining raw materials are strictly consistent with those of Example 1, including multi-grade continuously graded high-alumina aggregate, 200-mesh andalusite micro-expansion component, CA-80 low-calcium high-alumina cement, and various auxiliary additives. Meanwhile, the preparation process also follows the same scheme as Example 1, namely, using the same premixing, vibration molding, and constant temperature and humidity curing process, and implementing a five-stage symmetrical gradient baking regime including low-temperature dehydration, medium-temperature stabilization, medium-high temperature uniform sintering, high-temperature steady-state densification, and symmetrical closed slow cooling. The diagonal temperature difference is also maintained at ≤15℃ throughout the process. This strict single-variable control design ensures that the degradation of the final product performance is only attributed to the lack of α-Al2O3 component, thereby enabling accurate assessment of the technical contribution of this creep-resistant ultrafine powder.
[0036] Testing revealed that the wide-temperature-range, deformation-resistant high-alumina liner preform prepared in this comparative example showed little difference in performance compared to Example 1 at room and medium temperatures, but exhibited significant structural defects under high-temperature service conditions. Its bulk density was 2.71 g / cm³, the density difference across the entire range was 0.02 g / cm³, and the linear shrinkage rate after reheating at 1550℃ for 3 hours was +0.09%, indicating that the material's densification and sintering shrinkage compensation mechanisms remained functioning normally. However, its high-temperature flexural strength at 1500℃ dropped sharply to 3.2 MPa, only 47% of the level in Example 1. More seriously, in the creep test at 1580℃ for 3 hours, the sample showed significant plastic deformation, with a creep rate reaching 0.85%, far exceeding the 0.2% safety threshold allowed for engineering applications. Furthermore, slight bulging marks due to high-temperature softening were visible on the sample surface after cooling. This indicates that although the micro-expansion effect of andalusite offsets the sintering shrinkage and ensures the basic stability of the dimensions, the material loses its ability to resist external loads and its own gravity deformation when it approaches the upper limit of the service temperature.
[0037] From a microscopic perspective, the fundamental cause of the aforementioned high-temperature failure phenomenon lies in the lack of reinforcement of the matrix ceramic bonding network by α-Al₂O₃ ultrafine powder. During the high-temperature sintering process of wide-temperature-range deformation-resistant high-alumina liner preforms, α-Al₂O₃, as a highly active ultrafine powder, not only fills the tiny pores between aggregates, but more importantly, it undergoes an in-situ solid-phase reaction with SiO₂ and α-Al₂O₃ in the matrix above 1200℃, generating a well-developed mullite or corundum-mullite interwoven network. This in-situ generated ceramic bonding phase possesses extremely high melting points and high-temperature strength, effectively "pinning" grain boundaries and hindering grain boundary slippage and viscous flow of the liquid phase at high temperatures, thereby endowing the material with excellent creep resistance. In this comparative example, due to the lack of this crucial active reinforcing component, the matrix binding phase mainly relied on the CA2 or CA6 phases derived from the hydration products of low-calcium, high-alumina cement. Although this avoided the formation of low-melting-point calcium feldspar, under extreme conditions of 1580℃, the cement binding phase alone could not provide sufficient skeletal support, leading to viscous rheology of the matrix under high-temperature stress. This negative result strongly demonstrates that, under a wide temperature range of 1200℃ to 1580℃, α-Al2O3 creep-resistant ultrafine powder is not an ordinary filler, but an indispensable core functional component for constructing a high-temperature, strong, and tough skeleton and ensuring the creep resistance of precast components.
[0038] Comparative Example 3 This comparative example aims to verify the crucial role of the five-stage symmetrical gradient baking process in the preparation of wide-temperature-range, deformation-resistant molded high-alumina liner precast components. By comparing with Example 1, it examines whether the precast components can still maintain dimensional stability when using a traditional asymmetrical baking process, even with correct material formulation. Specifically, in this comparative example, the formulation system of the raw materials is strictly consistent with that of Example 1, using the same multi-stage continuously graded high-alumina aggregate, andalusite micro-expansion component, α-Al2O3 creep-resistant ultrafine powder, CA-80 low-calcium high-alumina cement, and various auxiliary additives. Furthermore, the premixing, stirring, vibration molding, and constant temperature and humidity curing processes are also completely based on the parameter settings of Example 1. However, in the baking process, this comparative example abandoned the five-stage symmetrical gradient baking system and instead adopted the traditional rapid heating and natural cooling process: the temperature was directly raised from room temperature to 1580℃ at a rate of 35℃ / h, without any constant temperature heating platform in between; after holding at this temperature for 4 hours, the kiln door was opened for natural cooling, and the cooling rate fluctuated with the ambient temperature and was generally much greater than 15℃ / h; throughout the entire heating and cooling process, the temperature field inside the furnace was not symmetrically controlled, nor was the diagonal temperature difference monitored or limited, and the maximum diagonal temperature difference inside the furnace was measured to reach 55℃.
[0039] Testing revealed that the wide-temperature-range, deformation-resistant high-alumina liner preform prepared in this comparative example exhibited severe defects in appearance quality and dimensional accuracy. Although its bulk density was 2.71 g / cm³, close to that of Example 1, indicating that the material's densification potential was not lost, the liner showed significant diagonal distortion after baking and cooling, with a difference in length between the two diagonals reaching 6.2 mm, a flatness deviation exceeding 4 mm, and multiple microcracks caused by thermal stress concentration visible at the corners and edges of the plate. Furthermore, X-ray diffraction analysis revealed extremely uneven distribution of residual stress within the preform, with local stress peaks reaching 12 MPa, far exceeding the safety threshold. These results clearly demonstrate that even with the inclusion of andalusite to offset sintering shrinkage and α-Al₂O₃ to strengthen the high-temperature skeleton in the formulation, without a matching symmetrical gradient baking process, the preform cannot avoid diagonal deformation and cracking failure.
[0040] From a microscopic perspective, analyzing the synchronicity of thermal stress release, the aforementioned failure phenomena stem from the asymmetric thermal field and thermal shock caused by the traditional baking process. First, the rapid heating rate of 35℃ / h far exceeds the response speed of heat conduction within the preform, resulting in a huge instantaneous temperature difference between the surface and core of the preform, and between the heated and unheated surfaces. This triggers asynchronous thermal expansion, and this expansion difference accumulates a large amount of elastic strain energy within the material. Second, during the high-temperature holding stage, the diagonal temperature difference of up to 55℃ causes a significant discrepancy between the sintering reaction rate and the andalusite phase transformation expansion process in different parts of the plate. The shrinkage that should have been uniformly compensated by the material is spatially misaligned, causing the matrix bonding network to bear shear stress before it is fully densified. Finally, the rapid and uneven cooling caused by natural cooling after opening the furnace door causes the surface of the preform to shrink and harden rapidly while the core remains in a high-temperature plastic state. The core shrinkage in the later stages of cooling is strongly constrained by the solidified surface layer, ultimately releasing the thermal stress in the form of permanent deformation or cracks. This negative result strongly demonstrates that for large-size, wide-temperature-range, deformation-resistant molded high-alumina liner preforms, optimizing the material formula is only a basic condition for achieving deformation resistance. It must be supplemented by five-segment symmetrical gradient baking and strict diagonal temperature difference control to ensure the synchronous release and uniform elimination of thermal stress throughout the entire process.
[0041] The above description is merely a specific implementation of this application, but the scope of protection of this application is not limited thereto.
Claims
1. A wide-temperature-range, deformation-resistant, die-cast high-alumina liner preform, characterized in that, Based on a total dry weight of 100%, the raw materials for preparation include: High-alumina aggregate: 70%~90%; Micro-expanded components: 3%~10%; Anti-creep ultrafine powder 1%~8%; Low-calcium binder 4%~10%.
2. The wide-temperature-range, deformation-resistant, die-cast high-alumina liner preform according to claim 1, characterized in that, The micro-expansion component includes andalusite; the creep-resistant ultrafine powder includes α-Al2O3; the low-calcium binder includes low-calcium high-alumina cement, wherein the mass percentage of Al2O3 in the low-calcium high-alumina cement is ≥80%.
3. The wide-temperature-range, deformation-resistant, die-cast high-alumina liner preform according to claim 2, characterized in that, Based on the total dry weight of 100%, the content of andalusite is 4%~8%, and the particle size is 150~250 mesh; the content of α-Al2O3 is 2%~5%, and the particle size is 1000~1500 mesh; the content of low-calcium high-alumina cement is 5%~8%.
4. The wide-temperature-range, deformation-resistant die-cast high-alumina liner preform according to claim 1, characterized in that, The high-alumina aggregate includes a multi-stage continuous gradation structure, which includes coarse aggregate, medium aggregate, fine aggregate, and high-alumina fine powder. Based on the total weight of dry materials (100%), the coarse aggregate has a particle size of 3-5 mm and a content of 15%-30%; the medium aggregate has a particle size of 1-3 mm and a content of 15%-35%; the fine aggregate has a particle size of 0-1 mm and a content of 10%-25%; and the high-alumina fine powder has a particle size of 200-400 mesh and a content of 10%-20%.
5. The wide-temperature-range, deformation-resistant die-cast high-alumina liner preform according to claim 4, characterized in that, Based on the total weight of dry materials (100%), the content of coarse aggregate is 20%~26%; the content of medium aggregate is 22%~28%; the content of fine aggregate is 16%~22%; and the content of high-alumina fine powder is 12%~18%.
6. The wide-temperature-range, deformation-resistant die-cast high-alumina liner preform according to claim 3, characterized in that, Based on the total weight of dry materials as 100%, the raw materials for preparation also include: Silicon micropowder 0.5%~2%; Composite water-reducing agent: 0.1%~0.5%; High-temperature resistant and explosion-proof fiber: 0.1%~0.5%; Curing uniformity regulator: 0.5%~2%.
7. The wide-temperature-range, deformation-resistant die-cast high-alumina liner preform according to claim 6, characterized in that, The bulk density of the wide-temperature-range, deformation-resistant, die-cast high-alumina liner preform is ≥2.65g / cm³, the density difference across the entire range is ≤0.02g / cm³, and the linear change rate after reheating at 1550℃ for 3 hours is within ±0.12%.
8. The wide-temperature-range, deformation-resistant die-cast high-alumina liner preform according to claim 7, characterized in that, The wide-temperature-range, deformation-resistant die-cast high-alumina liner preform is a die-cast high-alumina liner, and the die-cast high-alumina liner is a large-size rectangular structure.
9. A method for preparing a wide-temperature-range, deformation-resistant, die-cast high-alumina liner preform as described in any one of claims 1 to 8, characterized in that, include: The raw materials are premixed and stirred to obtain a mixture; The mixture is subjected to vibration molding and constant temperature and humidity curing to obtain a preform blank; The preform blank is subjected to five-segment symmetrical gradient baking to obtain the wide-temperature-range deformation-resistant die-cast high-alumina liner preform. The five-segment symmetrical gradient baking process includes, in sequence: The low-temperature dehydration section has a temperature range from room temperature to 200℃. The medium-temperature stable range is from 200℃ to 600℃; The medium-high temperature uniform sintering section has a temperature range of 600℃ to 1200℃; The high-temperature steady-state dense section has a temperature range of 1200℃ to 1580℃. The symmetrical, sealed, slow-cooling section has a temperature range of 1580℃ to room temperature.
10. The preparation method according to claim 9, characterized in that, In the aforementioned five-segment symmetrical gradient baking: The heating rate of the low-temperature dehydration section is 8~12℃ / h, and the holding time is 1~3h; The heating rate of the medium-temperature stable section is 15~20℃ / h, and the isothermal time is 2~4h; The heating rate of the medium-high temperature uniform sintering section is 20~25℃ / h; The heating rate of the high-temperature steady-state dense section is 12~18℃ / h, and the holding time is 3~5h; The cooling rate of the symmetrical closed slow cooling section is ≤15℃ / h; Throughout the five-segment symmetrical gradient baking process, the diagonal temperature difference is controlled to be ≤15℃.
